Economic Valuation of Ecotourism Management in The North Mareje Mountain Forest Area, Central Lombok District, Indonesia - Nawari Nawari; Isjoni Isjoni; Zulkarnaini Zulkarnaini; Almadi Syahza; Yusni Ikhwan Siregar (Riau University, 2021)
Ecotourism management of North Mareje Mountain Forest Area (NMMFA) is one of ways to achieved sustainable development goals (SDGs) in Central Lombok District. The lack of ecotourism economics value information causes investment for its development runs relative slowly. This study aims to valuate and evaluate the economics value of ecotourism development in NMMFA. The data used in this study includes number of tourist visits during 2018-2019, tourists visit frequency, travel costs and their socio-economic characteristics. Data was collected by interviewing NMMFA’s managers and tourists using questionnaire. Economic valuation analysis was carried out by using the traveling cost method (TCM). Economic evaluation diagnosed using paired t-test by comparing observed versus potential economic values. The Analysis result shows that the willingness to pay (WTP) of tourists whom visit to NMMFA=IDR. 347.579/visit with economic value = IDR 3,72 B/year. The economic evaluation results explains that the observed economic value = IDR. 986,78 M/year is smaller than the potential economic value of it carrying capacity ones =IDR 127,05 B/year. To improve economic development, it required a new paradigm of forest management by making current conservation activities become a conservation business and improving sustainable ecotourism management aspects.